2007
DOI: 10.1103/physrevlett.99.184502
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent Transport of Material Particles: An Experimental Study of Finite Size Effects

Abstract: We use an acoustic Lagrangian tracking technique, particularly adapted to measurements in open flows, and a versatile material particles generator (in the form of soap bubbles with adjustable size and density) to characterize Lagrangian statistics of finite sized, neutrally bouyant, particles transported in an isotropic turbulent flow of air. We vary the size of the particles in a range corresponding to turbulent inertial scales and explore how the turbulent forcing experienced by the particles depends on thei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

31
187
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 146 publications
(225 citation statements)
references
References 22 publications
31
187
7
Order By: Relevance
“…Even with this loading density, we calculate that interactions between the tracer particles are generally negligible. As mentioned above, our flow is not turbulent, even though the carrier flows studied both in simulation [8,13,14] and experiment [9][10][11]15] are typically turbulent. In previous work, the particle size is typically assumed to be smaller than the Kolmogorov length scale.…”
mentioning
confidence: 89%
See 4 more Smart Citations
“…Even with this loading density, we calculate that interactions between the tracer particles are generally negligible. As mentioned above, our flow is not turbulent, even though the carrier flows studied both in simulation [8,13,14] and experiment [9][10][11]15] are typically turbulent. In previous work, the particle size is typically assumed to be smaller than the Kolmogorov length scale.…”
mentioning
confidence: 89%
“…For particles with St > 0:1, previous studies have found that the acceleration statistics of inertial particles differ from those of fluid elements, for both heavy [8,9] and large particles [7,10]. In each case, the acceleration variance decreased as the Stokes number increased; for the heavy particles, the acceleration probability density function (PDF) also became narrower for higher St.…”
mentioning
confidence: 97%
See 3 more Smart Citations